2021
DOI: 10.48550/arxiv.2102.03821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lie complexity of words

Jason P. Bell,
Jeffrey Shallit

Abstract: Given a finite alphabet Σ and a right-infinite word w over Σ, we define the Lie complexity function Lw : N → N, whose value at n is the number of conjugacy classes (under cyclic shift) of length-n factors x of w with the property that every element of the conjugacy class appears in w.We show that the Lie complexity function is uniformly bounded for words with linear factor complexity, and as a result we show that words of linear factor complexity have at most finitely many primitive factors y with the property… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In fact, finiteness of Per(w) holds for every word of linear factor complexity [3], without requiring the assumption that w be recurrent, although the bound will not, in general, be as good as the one we obtain in the recurrent case.…”
Section: Words Of Linear Factor Complexitymentioning
confidence: 80%
See 2 more Smart Citations
“…In fact, finiteness of Per(w) holds for every word of linear factor complexity [3], without requiring the assumption that w be recurrent, although the bound will not, in general, be as good as the one we obtain in the recurrent case.…”
Section: Words Of Linear Factor Complexitymentioning
confidence: 80%
“…Upper bounds for Per(w) have been obtained previously [3], where it is shown that #Per(w) ≤ lim sup n→∞ p w (n + 1) − p w (n) + 1, which a result of Cassaigne [7] shows is finite when w has linear factor complexity. Bounds for Per(w) had been previously considered in other contexts [11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The following result appears in earlier work of the authors [3, Theorem 1.2], but we give a simpler and more self-contained proof here. We note, however, that the following proof does not recover the upper bound on the number of primitive factors that can occur with unbounded exponent (up to cyclic equivalence), which was given in [3].…”
Section: First-order Logicmentioning
confidence: 85%
“…Kobayashi and Otto [18] gave an efficient algorithm to test the repetitivity of a pure morphic word. Klouda and Starosta [15] showed further that every pure morphic word x is discrete, while the authors [3] proved that words of linear factor complexity are discrete.…”
Section: Repetitive Wordsmentioning
confidence: 99%